2008
DOI: 10.1007/s10741-008-9119-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological consequences of the TRα1 aporeceptor state

Abstract: Many patients have been characterized harboring a mutation in thyroid hormone receptor (TR) beta. Surprisingly none has yet been identified carrying a mutation in TRalpha1. To facilitate the identification of such patients, several animal models with a mutant TRalpha1 have been generated. While some phenotypic characteristics, such as an adult euthyroidism, are similar in the mutant mice, other aspects such as metabolism are quite variable. This review summarizes the most important consequences of a mutation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, more recent studies on TH control of cardiovascular function revealed an additional central mechanism originating in the hypothalamus. Mittag et al [70] reported that mice expressing the mutant TRα1 exhibit a slight decrease in heart rate and a severely impaired cardiovascular response to stress or an environmental temperature challenge. This cardiac dysfunction in TRα1-mutant mice was found to be due to an unbalanced sympatho-vagal tone from the brain [70].…”
Section: Systemic Effects Of Intrahypothalamic Thmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent studies on TH control of cardiovascular function revealed an additional central mechanism originating in the hypothalamus. Mittag et al [70] reported that mice expressing the mutant TRα1 exhibit a slight decrease in heart rate and a severely impaired cardiovascular response to stress or an environmental temperature challenge. This cardiac dysfunction in TRα1-mutant mice was found to be due to an unbalanced sympatho-vagal tone from the brain [70].…”
Section: Systemic Effects Of Intrahypothalamic Thmentioning
confidence: 99%
“…Mittag et al [70] reported that mice expressing the mutant TRα1 exhibit a slight decrease in heart rate and a severely impaired cardiovascular response to stress or an environmental temperature challenge. This cardiac dysfunction in TRα1-mutant mice was found to be due to an unbalanced sympatho-vagal tone from the brain [70]. Further studies indicated that a previously unknown population of parvalbuminergic neurons in the anterior hypothalamic area may be responsible for this dysregulation of heart function.…”
Section: Systemic Effects Of Intrahypothalamic Thmentioning
confidence: 99%
“…Analyses of mice heterozygous for a mutant TRα1, however, suggest that these patients might display normal TH economy, which could hinder their identification [10]. Despite the several defects observed in the animals with a mutant TRα1 (for a review see [11]), a reliable biochemical marker for a large-scale screening approach is missing. Although recent studies on TRα1R384C mutant mice revealed a TRα1-specific regulation of serum selenium (Se) [12], this parameter alone is not suitable to predict or diagnose RTH as it varies with serum TH levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, TH are thought to act principally by binding to their nuclear receptors, it is intriguing why TR knockout animals exhibit a much milder phenotype compared to hypothyroid animals (Gothe et al 1999). These differences in the phenotypes have been attributed to the unliganded TRs and their bound co-repressors in the pathogenesis of hypothyroidism-induced brain abnormalities (Hashimoto et al 2001, Morte et al 2002, Venero et al 2005, Kapoor et al 2010, Mittag et al 2010, Bernal & Morte 2013, Shi 2013. Since HDACs are associated with the co-repressors bound unliganded TRs, we hypothesized that inhibiting HDAC activity would block the negative regulation of target genes by unliganded TRs and may restore normal brain development under hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%